2003
DOI: 10.1152/ajpcell.00111.2002
|View full text |Cite
|
Sign up to set email alerts
|

Expression of multiple connexins in the rat epididymis indicates a complex regulation of gap junctional communication

Abstract: In the epididymis, Cx43 forms gap junctions between principal and basal cells but not between adjacent principal cells. Cx30.3, 31.1, and 32 were identified in adult rat epididymis by RT-PCR, whereas Cx26 was present in young rats. Postnatal development studies indicate that Cx26 mRNA was detectable only in the caput-corpus region of the epididymis and that levels increased by fivefold during the first 4 wk postnatally, when epithelial cells differentiate, and decrease to nondetectable levels thereafter. Cx31.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
54
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 35 publications
11
54
1
3
Order By: Relevance
“…However, the expression of Cx26 was not observed in the IS (Seo et al, 2010), implying functional discrimination between the IS and the rest of the epididymis. Expression patterns of some Cx genes in the epididymis during the first 3 months of the postnatal period were examined by Dufresne et al (2003). Similar to our current and previous findings (Han and Lee, 2013), they reported differential expression patterns of Cx26, Cx31.1, Cx32, and Cx43 between the head of the epididymis and the cauda epididymis .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, the expression of Cx26 was not observed in the IS (Seo et al, 2010), implying functional discrimination between the IS and the rest of the epididymis. Expression patterns of some Cx genes in the epididymis during the first 3 months of the postnatal period were examined by Dufresne et al (2003). Similar to our current and previous findings (Han and Lee, 2013), they reported differential expression patterns of Cx26, Cx31.1, Cx32, and Cx43 between the head of the epididymis and the cauda epididymis .…”
Section: Discussionsupporting
confidence: 83%
“…The presence of several Cxs transcripts in the epididymis has been evaluated in previous studies (Cry, 2011;Han and Lee, 2013). These Cxs include Cx26, Cx30.3,Cx31,Cx31.1,Cx32,Cx37,Cx40,Cx43,and Cx45. Comparison analyses of Cx genes expression between the head and tail part of the epididymis from 7 to 91 days of postnatal age conducted by Dufresne et al (2003) demonstrated segmental-specific and postnatal age-differentiated expression patterns of Cx genes in the epididymis. The epididymis is divided into an initial segment (IS), caput epididymis (head), corpus epididymis (body), and cauda epididymis (tail) based on morphological and functional aspects (Arrotéia et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…Indeed, our present study shows the expression change of several Cx isoforms in the caput epididymis at different postnatal ages. Dufresne et al (2003) have also demonstrated similar findings in the rat epididymis.…”
Section: Direct Intercellular Communication Throughsupporting
confidence: 72%
“…The localization of Cx isoforms in the epididymis has been studied (Cyr et al, 1996;Dufresne et al, 2003). Cx43 is between the principal and basal cells in the caput epididymis and does not exist between adjacent principal cells (Cyr et al, 1996).…”
Section: Direct Intercellular Communication Throughmentioning
confidence: 99%
“…67 Adherens junctions, desmosomes and gap junctions are found in the epididymis. 61,62,68 Of the connexins considered primary tumour suppressors, Cx26, Cx32 69 and Cx43 70 have been localized in the gap junctions of the rat epididymis.…”
Section: Other Junctionsmentioning
confidence: 99%